Relationships Between Hostility, Resilience and Intolerance of Uncertainty: A Structural Equation Modeling - Parlak, Simel; Tunç, Emine Burcu; Eryiğit, Derya; Uluman, Müge (Cluj University Press, 2022)
The aim of this study is to examine the relationship between hostility, resilience, and intolerance of uncertainty within the framework of structural equation modeling. In order to determine the relationship between the concepts, structural equation modeling was made, and the mediation role of resilience between hostility and intolerance of uncertainty was investigated. A total of 359 individuals participated in the study from different regions of Turkey. The short version of the intolerance of uncertainty scale, brief resilience scale, and hostility in pandemic scale were used as research instruments. The test of the measurement model resulted in an acceptable fit to the data, and all loadings of the measured variables on the latent constructs were statistically significant. The test of the direct relationship between hostility and intolerance of uncertainty model and mediation role of resilience between hostility and intolerance of uncertainty resulted in an acceptable fit to the data. The results of the Bootstrap analysis were used to determine whether the mediation role of resilience between hostility and intolerance of uncertainty was statistically significant. According to the results of the research, it is determined that psychological resilience is a partial mediator variable between hostility and intolerance to uncertainty. In order to control the feelings of intolerance and hostility toward uncertainty, which are risky for the psychological health of individuals during the Covid-19 pandemic, the protective intervention factors of improving psychological resilience and increasing the capacity to tolerate uncertainty should be addressed in terms of individual and social mental health.
Keywords: COVID-19; Hostility; Intolerance of uncertainty; Mediation model; Resilience